2015
DOI: 10.1590/01000683rbcs20140498
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Fractions in a Quartzipsamment Under Cultivation of Irrigated Mango in the Lower São Francisco Valley Region, Brazil

Abstract: aBstractimproper land use has lead to deterioration and depletion of natural resources, as well as a significant decline in agricultural production, due to decreased soil quality. Removal of native vegetation to make way for agricultural crops, often managed inadequately, results in soil disruption, decreased nutrient availability, and decomposition of soil organic matter, making sustainable agricultural production unviable. Thus, the aim of the present study was to evaluate the impact of growing irrigated man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
3
3
0
Order By: Relevance
“…Along with the simulated SWC and T soil conditions, litterfall determined inputs to the SCM from which heterotrophic respiration ( R h ) fluxes were simulated (Figure b). Simulated carbon amounts in the litter and microbial biomass pools ranged from 20 to 200 g C m −2 and from 70 to 130 g C m −2 , respectively, whereas the carbon amount in the humus pool remained relatively stable at 895–900 g C m −2 during the study period, similar to measured values in semiarid shrublands (e.g., Bolton, Smith, & Link, ; Cardoso et al, ; Cheng et al, ; Goberna et al, ). As expected, low amounts of R h occur during the winter and spring and increase substantially after the first rainfall event during the NAM due to the available SWC and labile substrate, consistent with Verduzco et al () and Zhang et al ().…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Along with the simulated SWC and T soil conditions, litterfall determined inputs to the SCM from which heterotrophic respiration ( R h ) fluxes were simulated (Figure b). Simulated carbon amounts in the litter and microbial biomass pools ranged from 20 to 200 g C m −2 and from 70 to 130 g C m −2 , respectively, whereas the carbon amount in the humus pool remained relatively stable at 895–900 g C m −2 during the study period, similar to measured values in semiarid shrublands (e.g., Bolton, Smith, & Link, ; Cardoso et al, ; Cheng et al, ; Goberna et al, ). As expected, low amounts of R h occur during the winter and spring and increase substantially after the first rainfall event during the NAM due to the available SWC and labile substrate, consistent with Verduzco et al () and Zhang et al ().…”
Section: Resultssupporting
confidence: 79%
“…the study period, similar to measured values in semiarid shrublands (e.g., Bolton, Smith, & Link, 1993;Cardoso et al, 2015;Cheng et al, 2015;Goberna et al, 2007). As expected, low amounts of R h occur during the winter and spring and increase substantially after the first rainfall event during the NAM due to the available SWC and labile substrate, consistent with Verduzco et al (2015) and Zhang et al (2014).…”
Section: Journal Ofsupporting
confidence: 87%
“…The recorded values of POC status were highest under orchards in our study which corroborates with many other findings (Gale et al 2000;Jamala and Oke 2013;Niaz et al 2017). This may be attributed to year-round decomposition of litter biomass and addition of root exudates as orchards have deep and well-developed root systems (Cardoso et al 2015). Thus, greater magnitude of POC under orchards, particularly the fruit trees, imparts a positive impact on stable C build-up (Guimaraes et al 2014).…”
Section: Effect Of Land-uses On Sequestered Soc and Its Poolssupporting
confidence: 90%
“…The similarity of TOC contents between PNV and EAC areas in the soil surface layer showed that increase in TOC content is favored by continuous deposition of litter and by the presence of more developed root systems on the surface (Cardoso et al 2015, Monroe et al 2016, which may contribute to maintain soil moisture and reduce soil erosion (Fultz et al 2013). In this study, the reduction of TOC in the DNV and CCC areas indicated that the soil preparation, which exposes SOM to weathering, and the lack of conservation practices in the CCC area have reduced physical protection of SOM and left the soil exposed to erosion (Melo et al 2016, Villarino et al 2017.…”
Section: Total Organic Carbon and Humic Fractions Of Organic Mattermentioning
confidence: 96%